Cucurbitacin D Overcomes Gefitinib Resistance by Blocking EGF Binding to EGFR and Inducing Cell Death in NSCLCs - Hong, Se Hyang; Ku, Jin Mo; Lim, Ye Seul; Lee, Seo Yeon; Kim, Ji Hye; Cheon, Chunhoo; Ko, Seong-Gyu (Frontiers in Oncology, 2020)
In this study, the mechanism of the anti-cancer effect through which cucurbitacin D (CuD) can overcome gefitinib resistance in NSCLC was investigated. Cell viability was measured by MTT assay, and cell migration and growth were observed by wound-healing and colony formation assays, respectively. Levels of EGFR family members, AKT, ERK, PARP and G2/M phase-related proteins were detected by western blot analysis. Immunofluorescence analysis was used to detect the intracellular expression of p-EGFR. Induction of apoptosis and cell cycle arrest was measured by flow cytometry. Solid-phase binding assays were used to determine binding to the EGFR family. CuD inhibits the phosphorylation of EGFR in gefitinib-resistant NSCLC cells and induces cell death via cell cycle arrest and apoptosis. CuD treatment or EGFR knockdown also suppressed the growth of gefitinib-resistant NSCLC cells. In addition, CuD overcame resistance by blocking EGF binding to EGFR in gefitinib-resistant NSCLC cells. In conclusion, we demonstrate that CuD overcomes gefitinib resistance by reducing the activation of EGFR-mediated survival in NSCLC and by inhibiting the combination of EGF and EGFR.